Türk ve dünya bankacılık sisteminde ihracat kredileri ile ihracat kredi sigorta/ garanti programlarının yeri ve ülke uygulamaları - Gülmüş, Faruk (My University, 2001)
There are many kinds of relationships between countries like political, economic, transporting, insurance, telecommunication etc. But one of the most perminent and active of these relationships is foreign trade, which means buying and selling goods. The basic conclusion of an economy theory, Traditional Comparative Superiority Theory, is free foreign trade. According to this theory, it is accepted that in economies where free foreign trade conditions are carried out, an unseen hand increases world's welfare in international commerce. But currently while globalization policies are defended, regional groups and commercial blocks arise. Each country implements some protective policies for protecting its economy and manufacturer/ exporters. These policies reduces effectiveness of export based industrialization and investment policies. The most important part of an open economy is export. Export means selling good or service to a country or transferring native goods abroad. Currently increase in importance and volume of international commerce year by year provokes national and international competition. Export and export-like operations can vary according to many factors like topography, culture, manufacturing technology, natural resources, capital and the level of organization.In accordance with this structure encouragement applications in export can vary in a wide spectrum in many aspects like areas, various dimensions, perminent / temporary style, in a general or sectoral base, in financial or economical areas. Developing countries have a lot of economical and social problems nowadays as they have the same problems in the past. Especially countries, which have managed to experience a quick development process after the 2nd World War, are the countries solved their financial problems. A lot of economies that carried out an intensive statist approach either considered globalization politics or instead of development they have regressed economically. Progress of developing countries depends on volume and distribution of their investments. But at this point the problem of financing of these investments arises. Countries want to reach to welfare of developed countries completing their economical development. In order to do this, it is needed to change economical structure without being afraid of change. Because resources are limited country faces with financial problems during investments. Therefore, with these limited resources it is impossible for a country to manufacture all goods and services that are needed in a closed economy and at the same time to maintain its development. Otherwise the concept of foreign trade would not formed. The most important feature of international commerce is to provide effective resource distribution between countries. Some of input that are needed for investment and manufacturing are gained from abroad. So foreign money income is needed in order to import and pay them in developing countries. In conclusion, it is a necessity to increase export incomes in order to perform developmental investments and reach to a good development rate. In export-based development models, there is an inter-stimulation mechanism between manufacturing and export. It is necessary to increase manufacturing for export which is accepted as locomotive of economy to reach to a particular level. And to discuss about an improvement or economic development, structure of economy should be changed and / or improved. In export-based development models, countries implement various encouragements within their own economic and social conditions in order to increase their export for short-term or change their export composition for long-term. But it doesn't seem possible for these countries to change economic structure by theirselves with current economic policies. They need resources. At first they try to meet resource need with modernization of manufacturing and marketing technologies. But resources in the world are a little and limited. It is not possible for a country to close its doors to the world and manufacture all goods and services it needs and develop. The countries, which try to develop, have to import machines, equipments, raw materials which are necessary for economic development and some of goods / services they can not manufacture on their own. At this point they need foreign trade. If foreign trade is applied and encouraged in accordance with resources and needs of the country it has many positive effects such as increasing resource supply, developing economy, increasing technological advance and development. Therefore it has been very important to increase export incomes quickly in order to reach a high development rate in countries that applying export based development model. Annual increase in net manufacturing in 1960-1990 was approximately 7-9 % in countries that use export-based development model like Taiwan, Hong Kong, South Corea and Singapour and this proportion was higher than 30 % of gross national product in 1980 in internal investments. This proportion reached to 47.6 % in Singapour. Although this proportion undulated in 1980-1990 period, it never decreased below 15 %. In Turkey, in the same period on increase was experienced in fixed capital investments. An important increase was experienced in export with 24 Jan 1980 decisions. Turkey gave up Import substitution development Policy and considered Export-Based Development Model in 24 Jan 1980 and in accordance with this model Turkey gave up fixed currency system and began to operate a realistic currency policy in order to increase effectiveness of resource distribution. Banks have been set free in detecting buying-selling floating currency with foreign money markets that has been organized as an interbank market since August 1988. Sometimes during stability policies interruption have been experienced in Turkey but after the last crisis floating currency system began to be discussed again. The main goal of this is to activate export and increase foreign money income. Following 24 Jan 1980 decisions, with 1983 regulations and policies export that was 2.261 billion USD in 1980 reached to 10.2 billion USD in 7 years. Within export-based development model there has been some changes in types of export. While the proportion of agriculture in export was approximately 65 % in 1979, it decreased to 20 %s in 1987. Currently this proportion is about 17 %s. And the proportion of industrial goods increased from 30 %s to 71 %s. Similarly types of countries that were exported have increased. While a great deal of export (total export was 2.260 million USD) was consisted of traditional agricultural commodities until 1980, with structural changes after 24 Jan decisions types of export goods and proportion of industrial products in export increased. Our foreign trade have had a shortage for years. This shortage is tried to be compansated by tourism incomes and foreign money our workers have sent from abroad. But these efforts were not success. Export incomes became the most and major resource of income without considering lendings from international institutions to balance of payment. So it became a necessity to increase export incomes in addition to worker and tourism incomes. In export-based development models that were stated above, manufacturing and export support each other in an interaction. Increase in export activates manufacturing and increases fixed investments. But the main point here is continuity of export. Encouragement for export should be applied to investment and manufacturing in a well balance. Export encouragements that are applied are tax returns, exceptions for taxes and fund. Tax returns have been applied as repayment of taxes that were taken directly or indirectly during manufacturing of industrial products to exporters. But tax return which is a direct encouragement was abolished according to subsidy contract that was signed in 1989 with GATT. In addition to these encouragements that were called as monetary encouragement some export policies such as exceptions for tax, duty, fee, tax of institutions in export, import with exemption for customs, residence fund exemption, increasing content of operations, services, sells that will make foreign money are operated in order to encourage actions for increasing export and foreign money. The other applicaitons for financial encouragement are export credit, guarantee and insurance operations that are called as Eximbank Credits. In this content it will be useful to discuss about effect of foreign trade especially for developing countries. Import of Capital Goods: Economic development depends on stock of capital goods. Stock of capital goods can be achieved by investments. Under developed countries can not provide raw material that requires advanced technology from their own resources. They have to import them. So they need foreign money income and they provide exterior payment primarily with export. Relieving Shortage of Savings: Countries which want to reach to a particular development rate, have to make investments. The source of investments is savings and they depend on national income. Generally in developing countries national income is low. In these countries export and foreign money income should be increased in order to relieve shortage of savings. Import of Technology: The one of benefits of foreign trade is that it is facilitating transferring of manufacturing technologies, management knowledge and know how which have been developed abroad. Using advanced techniques and encouraging manufacturing, effectiveness is provided in resource use. Discounting Shortage of Internal Markets: Technological investments can not be made for small organizations. Because internal markets are small, technological investments aren't made. Technological investments not only meet demands of internal markets but also require extending exterior markets. Limitations of internal markets can be overcome by directing export. Factor Operations:Capital can be collected by consistent foreign capital and foreign trade policies. Especially for countries of which population are primarily consisted of young people and so in which unemployment is seen commonly this problem can be solved by export of manpower. Increase in Competition: Foreign trade leads a competitive area that makes native manufacturers against foreigners. Free foreign trade prevents native manufacturers being monopolist and working ineffectively by creating competition and encourage them to follow-up newnesses. After realizing importance and positive effects of foreign trade on economic development, international commerce volume has been increasing year by year. As a result of this also agreement between countries has been increased. To maintain reached manufacturing level and provide and improve a continuous export, encouragement of finance of foreign trade especially finance of export has been arousen. Because regulations about encouragement are complex and comprehensive, we will outline them in this study. Encouragements are categorized like following: · Financial (about taxes) encouragements · Economic (structural) encouragements · Administrative encouragements The majority of financial encouragements are consisted of untaken or cancelled taxes, and charge that are paid during export and export- like operations and cost considerably. The majority of economic encouragements are consisted of finance credits with low interest rates and premium returns and VAT (value-added tax). Administrative encouragements may vary according to the content, way, time and even location of export. These encouragements may be seen as facilities and advantages which administration provide for export, exporter, sector or financial resources that are stated in export regimen statement, export official communique and regulations about credits or line commerce and infrastructural services like in fair and exhibitions. These efforts which are stated above for increasing export have been led to develop new techniques and methods to finance export and they have emphasized the importance of export credit insurance and guarantee system which mean meeting fund need in a cheap way and insuring export facilities. Especially bank and finance sectors which finance export for operating economy smoothly in investment -manufacturing- export circle and experiencing a quick and consistent development process have considered and developed finance techniques appropriate for exporters and system. Policies about export development are carried out in three categories, in other words three stages. They are: The first one is liberation which will be performed gradually in commerce and foreign money regulations. The second one is export encouragement policies that let use of financial support and concession. The third one is export finance program. This study will focus especially on export finance programs. So at first we will discuss export finance techniques, credits for export and financial tools. In this study we will discuss about export finance credits, export credit insurance and guarantee which are provided by Turkish Eximbank directly or indirectly via commercial banks before and after shipping Also we will investigate and evaluate four examples ( from the USA, Germany, France and Japan ). During process of foreign trade, exporters can face with some problems such as lack of information about financial structure and current status of exporter because exporter firm is abroad. Especially during process of forward sale when currency difference between the date of export operation and payment occurs against exporters, they face with foreign money loss. In these kind of sells, exporters also have commercial risk because of goods they sent to an unknown buyers and some political risk (also called country risk) which means risk originated from economic and political conditions in importer country. These risks cause a reduction in credited export and prevent exporters from providing credit for finance of credited export from banks. Therefore, in many countries some financial institutions that deal with credit, insurance and guarantee operations which minimize or eliminate commercial and political risks have been conducted. In these competitive conditions importer does not want to pay unless the goods are arrived him / her or he / she wants to choose the alternative payment plan that includes the longest duration. But seller (exporter) prefers to be paid as soon as possible to carry out other operations and provide finance for them. So nowadays considering the facilities of capital markets, payment on time even before time has many advantages. In order to provide it, some foreign trade payment methods and export finance techniques that will be good for both importer and exporter has been developed. Types of export finance can be classified in three groups. They are (as showed in figure 1) export finance according to risk, export finance according to aim and reason of use and export finance according to someone who finance is provided for. FINANCING EXPORT Without taking risk just with providing fund Financing before shipping Seller credit Without providing fund just with taking risk Financing after shipping Buyer credit Both with taking risk and providing fund Investment credit with export guarantee Line credit Short-term finance Relending Medium-term finance Long-term finance The main purpose of techniques related to before and after export operations is providing financial resources from international markets. The other methods used in export finance are leasing, factoring, forfaiting, export credit insurance / guarantee programs, financial clearing and mutual commerce. Export credit insurance is an insurance system that covers risks from manufacturing process to the date of payment. Export credit insurance is one of the export policy tools which increase export. It contributes to increasing export in two ways. First it insures exporter against importer and guarantees payment against commercial and political risks in particular limits. Second offering bank guarantee in export finance it provide credits exporters need. Credit word in export credit insurance means credibility which is perceived as a trust to buyer or its bank during period of transferring money to exporter or his bank accounts after shipping.. Insurance means undertaking the risk of nonpayment (or unabling to pay) by another institution and paying bill of export to exporter. Export credit insurance guarantees bills of export in case of nonpayment because of political and commercial risks and makes easier for exporters to provide finance from banks with this feature. Types of insurance policy vary according to country policies. In many insurance system Comprehensive insurance policies that include both political and commercial risks are used. Guarantee funds vary according to term of sell, type of insurance policy and quality of goods. And limits of this fund also vary with bill of export, contract and for whom this operation is made (exporter or government).In opposition of traditional insurance companies export credit insurance never gives 100% guarantee.So it forces exporter to select market and buyers carefully. In commercial risks guarantee varies between 80-90 % and in politic risks it varies between 90-95%. Although it is seen that some countries accept commercial and political risks as the same, this situation does not comply with the principles of the system. Approximate Guarantee Approximate Guarantee Countries % For Commercial Risks % For NonCommercial Risks % Avustralya % 90% 95 Almanya % 80% 85-90 Hindistan% 90% 90 ABD% 90% 90 Pakistan% 80% 90 Japonya % 60-80% 90 İsrail % 85% 95 Some advantages and disadvantages that export credit insurance will provide are following: Advantages: a? It eliminates the risk of nonpayment so protects exporter. This plays an important role in encouraging export. b? Operations are made with currency of the export date. So the firm shifts risk of currency difference to insurance firm. c? It will be easier (for exporter) to enter various markets with guarantee of export credit insurance. So problem of dependency on particular countries will be eliminated. d? Also small exporters will have encouraged with the guarantee of export credit insurance. Disadvantages: e? Export credit insurance is an application which requires government guarantee especially for political risks. Turkish Eximbank which makes export credit insurance in Turkey has been protected from politic and bureaucratic effects. Otherwise it will not be possible to expect a positive result from export credit insurance. f? Turkey usually tends to export to countries of which politic and commercial risks are minimum. Export credit insurance also should be directive and encouraging for entrance to Eastern, Middle East and African countries where risks are high, but also benefit rates are high. There are many export credit and insurance institutions in more than 40 countries in the world. The basic aim of these institutions is increasing export and supporting exporters in their country. In Turkey this institution is Turkish Eximbank which is an extension of Government (Offical) Investment Bank. Turkish Eximbank has been conducted to implement encouragement methods and techniques developed countries used and collect all functions in one hand in order to support our foreign trade, in accordance with current examples from the world. When total export was 2.261 million USD in 1979 this value reached to 10.190 million USD in 1987 as a result of facilitating operations with making easier particularly export operations generally foreign trade, increasing encouragement, adding new instruments into the system. During the period that open development model was applied, important changes have been seen in content of export in sector base; when the proportion of agriculture in total export was 59.4 % in 1979, this proportion reduced to 18.2 % in 1987; and when the proportion of industry in total export was 34.7 % in 1979 it reached to 79.1 % in 1987. In the same period important increases have been experienced in type of goods that were exported and number of country which was exported. As a result of these successes in export in an-eight-year period, the necessity for regulating foreign trade finance especially export finance was begun to discuss. As a result of this Official Investment Bank was converted into Turkish Export Credit Bank (Turkish Eximbank) with a decision of The Council of Ministers (17.06.1987, 8 no. 87 / 11914) in order to create an institution that would provide exporters export credit, finance guarantee, insurance for commercial and politic risks which would increase competition power of exporters to increase export and proportion of industrial goods in export and maintain a constant increase. (This decision was published in 21.08.1987 number 19551 Official Newspaper). Before this date in 31 March 1987 (law no. 3332). The Council of Ministers was empowered to reorganize Official Investment Bank about crediting, finance, supporting, insurance and guarantee of import and export, engineering services abroad, manufacturing and marketing external and internal investment goods. Finance programmes Turkish Eximbank implement are classified in these groups. (Figure 2 shows programmes of Turkish Eximbank.) Export Credits After Shipping which were accepted in credit progammes were connected with Export Credits Before Shipping in 1st Dec 1985. Export Credits Before Shipping are short-term credits that were implemented in 1st Dec 1985. Export Credits Before Shipping are short-term credits that were implemented in 1st March 1989 to support industrial sector which manufactures goods for export from manufacturing stage to export operation. Before Shipping Export Credits are used in various ways like it is showed in table 1. Before shipping (BS) export credits BS Turkish lira (TL) export credits BS foreign money (FM) export credits BS TL export credit BS FM export credit BS TL small and medium business ex.cr. BS FM small and medium business ex.cr. BS TL Development Priority Region ex. Cre. FIGURE 3 Before Shipping Turkish Lira and foreign money export credits are appropriated to banks so that they can offer it to exporter companies and manufacturer companies that manufact export goods (except for foreign trade capital companies) for goods that made in Turkey and are promised to be exported with foreign money (except for goods of which export is forbidden by law and regulations). Credit limits are appropriated as Turkish Liras for Before Shipping Export Credits and as USD for Before Shipping Foreign Money Export Credit to broker banks by Turkish Eximbank. Broker banks have to use min 5% and max 25% of general limits of Before Shipping Turkish Lira export credits in meeting demands of government and private sector and companies that maintain their commercial and economic actions in emerging regions. The resource that is needed for credit support Turkish Eximbank gives for export has been provided with successful getting into debt of Eximbank from native and foreign financial markets, new capital input (Nominal capital of Turkish Eximbank was increased to 50 trillion TL in August 1997) and internal sources that are created with effective use of existing sources. The nominal capital of the bank was increased to 50 trillion in August 1997. Turkish Eximbank has financed some of Turkish Liras credit programmes getting into debt from international markets since 1995 and financed foreign money credits getting into debt from national and international capital markets. Generally short-term credits are provided from national markets, to middle and long-term credits are provided from international markets because national resources are limited. The importance of borrowing from international markets has increased since 1994 financial crisis because commercial banks didn't want to offer cheap foreign money credit for exporters. In this period Eximbank borrowed 1 billion USD of foreign money reserve in commercial bank system and used this money for export. Eximbank borrows from international markets as submission to public, draft export as private plasman (bilateral loans), euro syndication credits and some other credits. In this manner Eximbank borrowed from Germany and Japan once, from euro markets twice as draft export and from Japan Eximbank 23 billion JYN for 14 years, from Canada EDC Institution 50 million USD as untied credit. Turkish Eximbank has very important roles in export finance. Because it is not a commercial bank, it fills a big gap in economy providing finance, guarantee and insurance support in all stages of export without any profit. Turkey has financed 45 % of its total export with programs which it has implemented up to now. When this was 9.42 % in 1989, it increased to 30 % in 1990, 39 % in 1993. Essential functions if Eximbank are support and encouragement of manufacturing selling of investment produces in order to improve export, to increase type of goods and services for export, to find new markets for export, to increase market rate of exporters in international commerce, to provide support for export operations, to increase the competition power of exporters, engineers and investors that work abroad and make country earn foreign money. Success in export area becomes perminent with the presence of a particular system that make exporters be able to compete in international markets and Export finance institutions of which financial structure is less vulnerable from economic crisis. One of the most important mutual features of export finance institutions in the world (Eximbank models) is that all of them are supported by government. Turkish Eximbank is an official finance institution. Eximbanks insure just commercial risks. They cover political risks in behalf of government. The support of government provides a resource flow from treasure and budget of government. When operation volume is big, government support effect international markets positively. In fact goals of all Eximbanks are the same. Their goal is to develop export with export policies, increase type of export goods, support exporters in invest rates, term and other financial tools and increase foreign money incomes and export. For these reasons, many expert financial institutions have been constituted for development export and its finance in more than 40 countries in the world. There are some differences in technique and practice between countries since export credit operations are based on financial system of country. But these differences have reduced between European Union Countries with globalization policies after 1990s. In this manner applications from four countries (the USA, Germany, France and Japan) which work in banking system were investigated and evaluated. When we see the USA, the USA provides finance of export not only with US Eximbank but also with PEPCO-OPIC-FCIA, CCC or many programs for finance, insurance and guarantee of export. The company which is given credit or guarantee may be native or foreign, all programs are conducted to support export of the USA. US Eximbank can give direct or indirect credit below interest rates of markets, so it neutralizes competition unequivalancy between countries. Also it provides finance to sell American goods (especially that requires a long-term) for foreigners. It also gives credit and guarantee to small and medium companies that have potential for export but can not sell abroad because of difficulties in manufacturing and marketing. The Export-Import Bank of the US, which was constituted in 1934 as an independent governmental organization, facilitates export with short and medium-term insurance, medium-long term credit and guarantee. The content of guarantee and insurance Eximbank offered has been arranged to protect exporters from politic and commercial risks. With financing sales of USA goods in Asia and Europe, US Eximbank has contributed to increase commerce in world and reconduct of economies that impaired after 2nd World War. By Marshall Plan, financial power of USA Eximbank has been directed to developing countries. But it is not let Eximbank give credit for military equipment or service to these countries. Military goods are provided by finance or guaranteed bank credits as a part of programs of Ministry of National Defence when Eximbank intends to finance all or some part of export, it must take permission from the USA Commission of Maritime.Otherwise export goods have to be carried by ships of the USA. When permission is taken, 50 % of financed goods may be carried by ships carrying flag of the country that makes import. But when Eximbank doesn't provide finance just gives guarantee, the necessity for carrying by ships with American flag will disappear. Repayment of Before Shipping export credits that are given by commerical banks in the USA to related financial institutions are guaranteed by Eximbank or insured by FCIA. FCIA (Foreign Credit Insurance Association) doesn't finance export. But insuring export incomes against politic and commercial risks it gives exporters the opportunity to take more and appropriate credits from banks or other institutions. FCIA was constituted in 1962. While private insurance companies were insuring claims in the USA, FCIA was constituted by Eximbank and approximately 65 private insurance companies. FCIA exports insurance policies in behalf of member companies and Eximbank. Insurance of FCIA covers 90 % of bill value out of exceptions. The rest, 10 % of bill is undertaken by exporter. FCIA insures commercial risks by itself and noncommerical risks by Eximbank in behalf of government. Without considering whether the company is native or foreign, all programs are designed to support export of the USA directly.These supports are offered with various programs by Eximbank of FCIA. GSM program is a credit program which is based on medium and long-term import of agricultural commodities and operated by CCC which was established to support export of American agricultural goods by USA government. CCC which was established for the purpose of stabilizing, supporting and protecting USA farm income and prices, of assisting in the maintenance of balanced and adequate supplies of agricultural commodities, products thereof, foods, feeds, and fibers, and of facilitating distribution of agricultural commodities operates two commercial guarantee programmes to assist US exporters of agricultural commodities. · GSM-102 programme finance export from 6 months to 3 years. · GSM-103 programme finance export from 3 years to 10 years. In GSM-102 just amount of FOB is covered by guarantee, in GSM-103 FOB and freight are covered. GSM-102 is for import of agricultural commodities, GSM-103 is for import of cattle. The goal of these programs is not donation or subsidy of food. The main goal is to lenghten term of commercial credits for finance of sells. In our country GSM-102 credits are generally used for cotton import and preferred term is 3 years GSM-102 credits. When finance is provided by USA bank 95 % of contract is insured. But USA bank covers rest of the risk (5 %), so it finance 100 % of contract. PEFCO (private export funding corporation) is a private corporation owned by 36 commercial banks, 6 industrial firms, and 3 financial services companies. PEFCO is a major source of capital for medium and long-term fixed-rate financing for US exports. PEFCO serves as a supplemental source of financing for foreign buyers of US goods and services. The high cost and long economic lives of some exports. For example, aircraft, industrial plants and conventional or nuclear power plants require long amounts of money for extended terms. The Overseas Private Investment Corporation (OPIC) is a US government agency that provides project financing, investment insurance and a variety of investor services in more than 135 developing nations and emerging economies throughout the world. OPIC encourages American overseas private investment in sound business projects that have a positive impact on the host country's economy and environment. When we investigate a German financial system, we see that development of German economy depends on financing of projects abroad to meet export of investment goods, abroad investments and needs of country. KFW which is a government agency in Germany finance export especially to underdeveloped and developing countries. But not only KFW but also the other commercial banks can provide finance with or without cooperation of KFW. But insurance and guarantee operations are made just by a private organization, HERMES. In Germany, export credits, insurance and guarantee programs are operated according to Budget Law. So government gives guarantee, insurance or finance just if export will be beneficialfor country or project / goods or services is worth encouraging. In this manner AKA and KFW export credit institutions undertake medium and long-term credits that exporters need. In Germany, export credit insurance service is given by Hermes-Kredietversicherung AG on behalf of government. Hermes provides export credit insurance for resident German exporters and banks. Hermes that was established in 1926 worked as a reassurance of government until 1949. Then Hermes began mutual operations with Treuarbeit AG, Wirt-Kredietversicherungs AG that was established by government. It is the biggest credit insurance company which have a large representative network in the world and 50 % of market rate in Germany. Annual premium income in 1999 was about 1 billion DM. Credit term varies according to type and variety of goods and service. Insurance is provided for consuming goods for 180 days, durable consuming goods for 2 years and capital goods for 5 years. Export finance is given by KFW. There is no maximum term for export credits, but absolutely Hermes should accept payment conditions. At first Hermes insurance is required for finance. This applicaiton shows how effective German government use export credit insurance as a tool of export encouragement. Also Hermes gives service of export credit insurance on behalf of government. AKA is an export credit institution that was established as a 56 bank consortium and focuses on financing of export for medium and long-term. After 2nd World War in 1948 KFW (Kreditanstalt für Wiederaugban) was established to activate German economy with low interest rated investment credits. Its main function is to finance the most emergent structural projects according to ERP (European Construction Program). KFW that is a government agency was constituted as an anonymous company according to national regulations. It has Directory and Audit Board. The main function of Directory Board is to manage resources. KFW is a bank that has politic and economic character. KFW acts like one kind of development bank for both national economy and developing country economies. On one hand it encourages German economy giving internal investment and export credit, on the other hand it gives credit and donation to developing countries on behalf of government according to German Financial Cooperation. But encouragement of internal economy gives precedence to financing of medium and long-term investments and projects of which primary goal is structural change to support economic policies of government. For these internal credits aim is to solve specific financial problems of small and medium companies and to increase their power of competition in national and international areas with making them more effective and more productive. In France export credit insurance is operated by COFACE (Compagnie Francaise d'Assurance pour le Commerce Exterieu). It was established in 1st June 1946 with Banque Francaise du Commerce Exterieus / Bfce. It is an anonymous company and its total capital is 300 million FF. Most of its stockholders are from general sector companies (banks and insurance companies). Its actions are divided into two groups: Commercial and finance operations and insurance operations. It also manages official credit insurance programs on behalf of government and provides insurance for risks of international commerce. On one hand, as a private organization COFACE guarantees short-term export credits against commercial risks; on the other hand it serves as an official agency with guarantees all export credit operations against commercial risks. In France, a close cooperation for export credits includes commercial banks and two governmental agencies, BFCE and COFACE. Like COFACE, BFCE acts on its own. When government needs, fixation mechanisms begin in accordance with general bank rules. When Financing of short-term export is provided by existing commercial banks, especially financing of medium and long-term export is carried out by BFCE -government agency-. But organization that carries out export credit insurance and guarantee programs is only COFACE. COFACE has a two-aspect-character. On one hand (as a private company) it insures short-term export credits against commercial risks. On the other hand (on behalf of government) it covers insurance of export credit operations against noncommercial risks. 90 % parts of goods which are wanted to be insured are expected to be produced in France. If it is produced in a country that is a member of European Union this proportion can be reduced up to 60 . BFCE is an organization that gives credit to export companies in France. It finances export goods with medium and long-term credits directly. In Japan, there are two important organizations that offer export related services. One of them is a government agency, Exim-Import Bank of Japan (EXIM); it credits to contribute to Japan export-import and finance large investment projects that cannot be financed by a commercial bank with various names and programs. EXIM is a government financial agency. It was established in 1950 with a law and began operations in 1951. One other institution, Ministry of International Trade and Industry (MITI) which offers various insurance policy to exporters and commercial banks insures just risks that cannot be insured within country lines. Also OECF that was established in 3 March 1961 in order to constitute economic collaboration with developing countries plays an important role in financing and encouragement of export. A STABİL EXPORT FOR A SUSTAİNABLE DEVELOPMENT A stabil export for a sustainable development depends on a consistent increase in investment and manufacturing and systematic export encouragement. The solution is long-term policies that require patience to meet positive results. It is not possible to increase export consistently and perminently via directing existing manufacturing abroad decreasing charges and increasing internal prices like Turkey's current applications. On 5 April 1994 a new packet of stability measures came into force, with these measures it was aimed to relieve internal imbalances and to construct external balances with increasing export and decreasing import. In 1993 when export was 15.3 billion USD, import increased to its highest level, 29.4 billion USD. Export-import proportion have decreased to the lowest level in this period since 1981. Defisit of foreign trade was 14.1 billion USD. The proportion of foreign trade to gross national product became 8 %. This situation have heavily affected stability measures of 1994. The main purpose of stability policies is increasing export, so they applied short and long-term measures for decreasing defisit of foreign trade. they sometimes applied devaluation which is a short-term measure that will work quickly like current stability policies they are applying. But long-term measures couldn't be applied adequately. Expected results couldn't be reached because of politic instability and Customs Union studies. And in 1995 when government reached to targeted numbers in export (21.6 billion USD), a big increase in import increased defisit of foreign trade to almost three times of 1995 results (import 35.7 billion USD, defisit of foreign trade: 14.1 billion USD). Parameters about our foreign trade has been shown in table 19. As it seen in table 19 approximately 1/ 3 of gross national product is consisted of import and export. Therefore export has became an integral part of our economy. Big and periodic increases in export are not important. The important thing is to provide a sustainable increase in export. In 1994 export increased 20 % comparing with the prior year and import decreased. When year 1994 had a good picture, the same performance couldn't be catched in 1995 and export began to be discussed in economy. There are still the same policies (increasing export, decreasing import) in the center of crisis that was experienced in 2000-2001 and stability policies. But point that has been forgotten is that export is direct related to investment and manufacturing. Manufacturing is a necessity to make export and investment is necessary to manufacture. New capacity increases stopped because government stopped manufacturing and government financial agencies stopped manufacturing and investment by current monetary and economic crisis. The reasons of export increase that has been experienced since 1980s are open development model and investments that had been made by governmental agencies until 1980s. Our performance in export always fluctuate and cannot reach to targeted level because of our efforts of which aim is to solve problems with short-term currency policies. And if we go on not to focus on other independent variables (export encouragement, investment, quality of goods, exterior demand, marketing, political preferences, manufacturing etc.) and not to support export investments, we always face with the problem of export ie balance of payment. There are investments that are performed in manufacturing industry in the core of successful export actions. Also barriers that prevent foreign capital flow have been eliminated and foreign capital has been directed to especially manufacturing industry and export. As it was stated above,it is not possible to make export stabil with encouraging policies and monetary policies.It is needed to apply flexible currency policy and measures that to will increase manufacturing and productivity such as education of manpower, choice of appropriate technologies etc. The second group measures are policies that will provide balance between encouragement which have been provided for export and import industries. Quota, schedule, obligations and foreign currency transactions limitations provide a high protection for import. And some facilities are provided for exporters such as tax return, exemption for tax, duty, fee, customs tax, foreign money appropriation and cheap credit. But encouragement of export with these ways led to an important loss in income in government budget. Because this situation also causes unequity in competition between countries, some institutions like GATT has opposed some applications. In fact the main condition for encouragement of export is liberation in import that will be made gradually in a planned period instead of limitations. These liberation policies will integrate national economy into world economy and provide economic resources to be used in a most effective way. As stated before, export plays an important role in economic development. Economic development means continuous increase in capital collection of country. So it is not possible to consider export apart from general economic structure of country. Export may be identified as an abroad extension to internal manufacturing. Economy of a country depends on its export. If adequate export couldn't be made, it will be necessary to seek for all kinds of resources for a particular import level that is required by economy. As it will be understood, there is a close relationship between economic development and foreign money. Because foreign money is a payment tool which make possible to import of machine / equipment and input that are necessary for investment and manufacturing and cannot be manufactured in country. The best way of not to experience shortage of foreign money is to increase export incomes. Otherwise country faces with problems. For example mistakes our country have made or have had to made for years is financing import with exterior borrowing. In a result of this, in recent years we have converted into a country that cannot make import and even pay interest rates of exterior borrowing. When all of these situations are considered financing of deficit of payment balance depends on just increasing and developing export quickly for Turkey. As we stated before, we have to increase types of export goods besides increase export. The only solution to prevent economic crisis and decrease load of exterior borrowing is to increase the proportion of industrial goods and service products in export in addition to traditional agricultural commodities. With a planned, imported industrialization strategy that has began to be operated in 1963, Turkey tried to have lasted in consuming and then in manufacturing crude and investment goods. But in result of economic and political crisis that were experienced in last 1970s, without completing this process, Turkey had to consider an export based industrialization model input that couldn't be reduced adequately has caused foreign trade always have a shortage. Turkey is a country that have industrialized and developed quickly after 1980s. Profile of exporters have changed from agricultural commodities to industrial goods. In a hard competitive area, export have directed to new markets and export with term has become a necessity for developing countries. This situation has led institutions to guarantee risks of export. Insurance is a security factor for economic and social life. For example currently it is not possible to make transfers, drive or buy a building or factory without insurance. This situation shows importance of insurance in economy in undertaking risk of loss, risks and providing economic balances. It is possible to compete in markets that are developed countries are dominent, to increase export of industrial goods, to decrease costs, develop industrial sector besides technologic advances and not to experience foreign money shortage, and for exporters to eliminate or minimize export risks with just using export credit insurance as an effective tool in export encouragement. Export credit insurance programs play a very important role in development of nontraditional export. It is seen that proportion of traditional export goods have decreased when proportion of textile, leather and iron-steel products has increased in result of Eport credit insurance programs of Eximbank especially after 1990. The most important factors that have led our exporters to extent to Middle Asian countries which is an important market for Turkey are Short-term Export Credit Insurance (March 1989) and After Shipping Political Risk Insurance which has been operated for countries with high political risk since 1996. Total amount of export that was made within short-term export credit insurance was 3.497 million USD in 1997. However, selling goods and services abroad causes a lot of problems for exporter. Exporters and companies that service abroad face with many risks except for commercial ones. In addition, problems that are faced oftenly are difficulties in collecting data about abroad company, their commercial capasities, liquidty indicators that shows payment ability and in following up continuously financial status and commercial operations. When we talk about internal sells, buyers don't face with information problems in general. Because two parties live within the same country and are subject to the same legislations. When comparing with internal sales, more problems are faced in extorior sales. The most important one of these problems is difficulties in commerce because of decisions of government not buyer or seller. For example buyer country can forbid import of a particular good, it may be impossible to make import bacause of transfer problems as a result of political events (war, rebellion or revolution). For these kind of reasons importance of export credit insurance have increased and it has become almost an obligation. In recent years Middle East, inlet and Northen African countries have intended to make investments in all sectors and opened investment areas to foreigners bacause of lack of technic and qualified people. As a result of this situation, a necessity of encouragement of Turkish companies that want to offer services like construction, engineering, assembling and consultancy has arousen. At first Turkish companies has served as subcontracter in construction sector, but in recent years they have begun to take jobs in industry. A lot of risks are faced with during export of services like export of goods. Although risk of nonpayment of service costs for Middle East and North Africa countries is lower because of their high petroleum incomes, the risk always exists. Especially export credit insurance became an important reliability resorce for exporter companies with protecitng them from economic risks (right loss because of slow burocrentic flow, lenghtening time of completion of works of uncontrollable reasons) and other risks such as revolution, internal war, natural disasters. But of course credited sales will carry a high risk. These political and commercial risks should be guaranteed within some rules. These insurance operations can be made by both government agencies and private institutions. The most important feature differing export credit insurance from other normal insurences is that this insurance covers just credit for value of export. So the most important characteristic of export credit insurance is not to cover physical loss or damages that are risks of classical insurance. Also one other characteristic is that reassurance is not valid for it. Export credit insurance provides an additional guarantee for exporters in taking credit from banks with insuring exprt investments and credits and insuring goods for fire, accident or transfer damages during manufacturing of export goods. Exporters have diffuculties in taking cheap credits from commercial banks. Banks demand financial guarantee to take credit. The most oftenly demanded guarantee is mortgage is accepted as a guarantee and facilitates credit use. Because credits that have been guaranteed by export credit insurance can be taken over by bakn, they give guarantee to banks and exporters and so develop international trade. Major users of export credit insurance are: · Exporters that export goods to a foreign country: To guarantee credit against political and commercial risks insuring exporters against importers. · Industrail exporters that manufacture and export goods that require a long-term: To guarantee value of export · Importers that have been given import credit by a particular country with buyer credit system. Also banksand broker credit institutions that play an effective role in export finance giving credit to exporters and importers benefit from export credit insurance. Areas that export credit insurance will be used in should be selected carefully. Difficulties in competing with strong companies in internationsl markets and distribution of limited resorces to goods that have no charge for competition will cause loss of effectiveness in encoragement. When export credit insurance insure credits that have been given to exporters, it carries a comprehensive invesitgation about political and commercial status of importer country. So it is necessary for export credit insurance institutions to collaorate with good information institutions. They investigate political and commercial status of importer country also with help of commercial attache. They make rich view of exporters in operations and contribute to make more conscious export. Export credit insurance is an encouraging factor after export link. But manufacturing and marketing of a good that is ready for export depends on economic policies. So export credits insurance is an encouragement tool that facilitates management of risks of export. Export credit insurance programs play a very important role in development of nontraditional export. It has been seen that the proportion of traditional export goods decreased and some export goods (textile, leather and iron-steel products) increased in result of export credit insurance programs that offered by Eximbank since 1990. The most important applications that provide exporters to extent Middle Asian countries which are important markets for Turkey nowadays are Short-Term Export Credit Insurance (March 1989) and Politic Risk Insurance After Shipping (196). Cost of total export that was made within Short-Term Export Credit Insurance was 3.497 million USD in 1997. Contributions of banks to export with credits are appreciated by institutions of export credit insurance and make institutions increase guarantee rates. A 5 point increase in compensation proportions is discussed in export insurance operations that are financed by a commercial bank in France. Banks also provide finance to exporters taking over their insurance policy. Therefore they will have undertaken credit and guaranteed with insurance. This kind of banks are generally export institutions in foreign trade and export even they may have a partnership with institutions of export credit insurance and so credit and insurance operations can be made easily in the same institution. In general it is accepted as a mission of government to increase and encourage export. Government has an important responsibility for both export credits and export credit insurance and guarantees. Export credit insurance not only contains commercial risks but also politic risks. At this point government is obliged to undertake both commercial and political risks because of lack of information. It is very difficult (for a private institution) to estimate about politic status and collect reliable information about a politic life of a country. The organization that can access these data in an easiest way is government so this condition forced government to play an active role in export credit insurance even it is liberal. SMALL AND MEDİUM ORGANİZATİONS Small and medium organizations have become an important part of recent economy and encouragement policies because of their contributions. Almost all countries attribute them an important role in economic development programs. So supportive policies that will provide them to manufacture with the newest technology, staff qualified manpower, develop systems which will get resources from financial markets and increase foreign trade should be carried out in a continuous and coordainated way. Eximbank operates export credit programs for small and medium organizations on both Turkish Lira and foreign money. It is an obligation for commercial banks to appropriate at least 30 % of credit limits to small and medium organizations. Otherwise they cannot offer all of credit limit. In 1999 Eximbank reached to 3.6-billion USD credit volume. 1.5 billion USD of total volume was given to small and middle-sized organizations. Number of company that was given credit 3160 (until September 2000) and 66 % (2077) of them were small and middle-sized organizations. In our country the reasons of why these organizations contribute to export in a limited way and have limited facilities for credits are problems that are experienced in finance, administration, marketing, technology development, education and organization. Lack of exterior demands, marketing and organization, insufficent manufacturing, inability in manufacturing goods that can make competition in exterior markets, difficulties in providing credits affect their export in a negative way. Their proportion in total export is 8 % in Turkey. This proportion is much higher in other countries in India 43 %, in Japan 38 %, in the USA 32 %, in Germany 31 % and in France 23 %, in two countries that generally support big institutions in accordance with economic policies, England and South Corea, 22 % and 20 %, respectively. But when we consider these organizations not only as an exporter but also a manufacturer that sell goods to exporters, this proportion (8 %) increases. The proprtion of small and medium organizations in total credit volume has been 3.5 % until 1990s, in last 5 years this proportion has reached to 8 %. This proportion is 43 % in the USA, 35 % in Germany, 50 % in Japan, 27 % in England and 47 % in South Corea. Although the proportion of small middle-sized organizations in manufacturing is 38 %, credits are just 8 %. These organizations have difficulties in providing credit because they cannot meet criteria of commercial banks with their existing financial structure. Since macro economic values are not stabilized, banking sector prefers meeting the needs of government with internal lending instead of offering credits to real sector especially to small and medium organizations. But important steps have been walked in order to overcome this problem after the crisis we experienced in 2001 and of which effects still go on. Because these organizations don't have an organized and translucent accountency system, an effective financial organization culture is not developed. During evaluation of companies banks, of course, consider balance and financial data. For these reasons, amount of credits that are given to these organizations remains in low levels. In addition, it is important for increasing types of export goods to direct these organizations into export goods which have trademark and high VAT. Especially textile and ready made clothes sectors should prefer expensive, high quality and marked goods instead of cheap and low quality ones. Export credit insurance is very important for small and medium organizations, but insurance should be made common and used as an effective encouragement tool. With export credit insurance small and medium organizations may have opportunities of meeting new buyers. We can consider export credit insurance as one kind of nonmonetary financial support. This feature is very important for exporter companies. For example; inability to collect cost of export (if 50000 USD) from Germany is a big problem for a small company. Since big companies can follow up credit easily, it won't be an important problem for it. So export credit insurance is very important especially for small companies. Competition is being harder day by day in the world. If you want to sell more and have larger markets you have to deliver goods in time, price and quality of goods have to be optimal and you have to provide finance with suitable terms to other party. Export credit insurance is a very important facility to overcome these conflicts and protect yourself from risks.
Keywords: Bankalar Ve Bankacılık; Ihracat